INOVASI TEKNOLOGI MATERIAL RAMAH LINGKUNGAN DALAM MENDUKUNG PERKEMBANGAN INFRASTRUKTUR TRANSPORTASI KERETA API - Wirawan, Willy Artha; Zulkarnain, Akbar; Rozaq, Fadli (CANTILEVER, 2019)
The development of infrastructure to support railway facilities requires innovation in materials that are lightweight, strong and environmentally safe.  The biocomposite is one of the innovations in engineering technology of new materials made of natural fibers.  In this study, the development of environmentally safe materials (biocomposite) was made by using bark fibers of waru trees.  The waru bark fibers were analyzed by varying the compositions of treatment: 0% chemicals, 6% of NaOH, and 0.75% of silane.  Afterwards, the waru bark fibers were formed using the vacuum infusion method by applying a polyester matrix.  In this study, several analyses had been conducted on fiber composition, SEM, and fracture area.  The results showed that the treatment of the structure of alkali-silane fibers (the content of lignin, cellulose, and hemicellulose), made the performance of materials better which had been proven by the decreased fracture area of 250.777 mm2.  The waru bark fiber biocomposite materials can be applied as an innovation in developing fiber replacement materials to support railway interior facilities that are cheaper and environmentally safe.